Relational needs satisfaction scale: reliability and validity study in Turkish - Toksoy, Şafak Ebru; Cerit, Cem; Aker, Ahmet Tamer; Zvelc, Gregor (Anadolu Psikiyatri Dergisi, 2020)
Abstract: Objective: The aim of this study was to evaluate the reliability and validity of the Relational Needs Satisfaction Scale (RNSS) in Turkish, an inventory that was developed based on Erskine’s Relational Needs Model. Methods: The study was conducted on a sample of 561 people, which consisted of students from faculties of Medicine, Engineering, Law, Fine Arts, Health Sciences and Sports Sciences as well as employees from Faculty of Medicine in Kocaeli University. Reliability and validity analyses were conducted after analysis of the linguistic equivalence of the scale. The construct validity of the scale was investigated using confirmatory factor analysis (CFA). Experiences in Close Relationships-Revised (ECR-R), Scale of Dimensions of Interpersonal Relationships (SDIR) and SelfCompassion Scale (SCS) were utilized to test convergent validity. To evaluate the reliability of the scale, test-retest correlation, Cronbach alfa and total item correlation were calculated. Findings: The five-factor structure and the hierarchical model was confirmed via CFA. Levels of fit indices were sufficient and acceptable for both the fivefactor model (?2/df=2.03, RMSEA=0.048, CFI=0.928, TLI=0.914, IFI=0.921, AIC=464.211) and the hierarchical model (corrected) (?2/df=2.05, RMSEA=0.048, CFI=0.924, TLI=0.912, IFI=0.925, AIC=468.610). Cronbach’s alpha reliability score was found to be 0.83, indicating that the internal consistency of the scale was high. The Turkish version of the scale contains 20 items just like the original one. Comparison of RNSS with ECR-R, SDIR and SCS revealed that convergent validity was ensured. Conclusion: In light of the findings, the Turkish version of the RNSS was concluded to be a reliable and valid measurement tool and it is suggested that it can be utilized in future research

Özet: Amaç: Bu araştırma ile Erskine’nin İlişkisel İhtiyaçlar Modeli temelinde geliştirilen bir ölçme aracı olan İlişkisel İhtiyaçlar Doyum Ölçeğinin (İİDÖ) Türkçe geçerlilik ve güvenilirliğinin değerlendirilmesi amaçlanmıştır. Yöntem: Çalışma, Kocaeli Üniversitesi’nin Tıp, Mühendislik, Hukuk, Güzel Sanatlar, Sağlık Bilimleri ve Spor Bilimleri Fakülteleri’nde okumakta olan öğrenciler ile Tıp Fakültesi çalışanlarından oluşan toplam 561 kişi ile yürütülmüştür. Ölçeğin dilsel eşdeğerliliği incelendikten sonra geçerlilik ve güvenilirlik çalışması yapılmıştır. Doğrulayıcı faktör analizi (DFA)kullanılarak ölçeğin yapı geçerliliği incelenmiştir. Ölçüt geçerliliği için Yakın İlişkilerde Yaşantılar Envanteri-II (YİYEII), Kişilerarası İlişki Boyutları Ölçeği (KİBÖ) ve Öz-Anlayış Ölçeği (ÖZANÖ) kullanılmıştır. Ölçeğin güvenilirliği için test-tekrar test, Cronbach alfa ve madde toplam korelasyon değerleri hesaplanmıştır. Bulgular: Ölçeğin beş faktörlü yapısı ve hiyerarşik model DFA ile doğrulanmıştır. Beş faktörlü modele ait uyum indekslerinin (?2/df=2.03, RMSEA= 0.048, CFI=0.928, TLI=0.914, IFI=0.921, AIC=464.211) ve hiyerarşik modele ait uyum indekslerinin (düzeltilmiş) (?2/df=2.05, RMSEA=0.048, CFI=0.924, TLI=0.912, IFI=0.925, AIC=468.610) yeterli ve kabul edilebilir düzeyde oldukları belirlenmiştir. Cronbach alfa güvenilirlik katsayısı 0.83 olarak bulunmuş ve ölçeğin yüksek derecede iç tutarlılığa sahip olduğu belirlenmiştir. Ölçeğin 20 maddeli özgün yapısı Türkçede de korunmuştur. RNSS puanlarının ölçüt geçerliliği için kullanılan YİYE-II, KİBÖ, ÖZANÖ ile istatistiksel açıdan anlamlı ilişkilerinin olduğu saptanmıştır. Sonuç: Bu verilere göre, RNSS geçerli ve güvenilir bir ölçme aracıdır ve ilgili araştırmalarda kullanılması önerilmektedir
Keywords: Relational Needs Satisfaction Scale; validity; reliability; relational needs; integrative psychotherapy; İlişkisel İhtiyaçlar Doyum Ölçeği; geçerlilik; güvenilirlik; ilişkisel ihtiyaçlar; integratif psikoterapi